Sudden cardiac death in young athletes: preparticipation screening for underlying cardiovascular abnormalities and approaches to prevention - Higgins, J. P.; Ananaba, I. E.; Higgins, C. L. (The Physician and Sportsmedicine, 2013)
The study of sudden cardiac death (SCD) in athletes has received more interest in the medical and lay press over the past few years. Professional athletes represent ideals of fitness and health, and the sudden death of prominent athletes can come as a shock. Underlying occult cardiovascular disorders are the most common cause of SCD in athletes. Unfortunately, because these disorders rarely present clinically, their initial manifestation is often a fatal event. Due to this, much attention has turned to both primary and secondary prevention. Primary prevention includes preparticipation screening and secondary prevention includes having automatic external defibrillators available at sporting events. This article summarizes the most common causes of athletic-related cardiac arrest and evaluates the screening methods used to screen for these conditions. The general sentiment is that we need to more effectively identify athletes who are at risk for SCD, but how to do so using an efficient screening system and in a cost-effective manner have not been determined.